Utilization of Personal Protective Equipment and Its Associated Factors Among Large Scale Factory Workers in Debre Berhan Town, Ethiopia - Birara Fekadie Baye; Minale Fekadie Baye; Abraham Teym; Behailu Tariku Derseh (SAGE Publishing, 2022)
Background: Personal protective equipment (PPE) is one of the safeguards to protect workers from occupational risks. The aim of this study was to assess the utilization of PPE and associated factors among large-scale factory workers in Debre Berhan city administration, Ethiopia. Methods: An institutional-based cross-sectional study was conducted using stratified sampling among large-scale factory workers in the Debre Berhan city administration. Four hundred thirty-two employees were interviewed using a stratified sampling technique from 7 large-scale factories. Logistic regression analysis was used to identify factors affecting the utilization of PPE. The strength of association between variables was measured using the odds ratio with 95% confidence intervals at a P -value of .05. Results: A total of 413 respondents were included in the study, with a response rate of 95.6%. Two hundred and eighty-two (68.3%) of the participants were males. The mean age of the respondents was 28.37 ± 7.33 years. The PPE utilization was 35.43% (95% CI: 0.31, 0.40). Accordingly on job training (AOR = 8.85; 95% CI: 5.52, 14.28), previous history of injury (AOR = 0.23; 95% CI: 0.14, 0.36), workplace supervision (AOR = 14.08; 95% CI: 7.87, 25.0), and availability of guideline (AOR = 4.62; 95% CI: 2.51, 8.49) were statistically significant with utilization of PPE among large scale factory workers at a P -value <.05. Conclusion: Utilization of PPE is low. Previous history of injuries, on-the-job training, supervision, and the availability of guidelines were all independent predictors of PPE utilization. As a result, job training, workplace supervision, root-cause learning, and the availability of guidelines should all be considered.